2022
DOI: 10.1111/lam.13665
|View full text |Cite
|
Sign up to set email alerts
|

Thymbra capitata essential oil has a significant antimicrobial activity against methicillin-resistant Staphylococcus aureus pre-formed biofilms

Abstract: Methicillin‐resistant Staphylococcus aureus (MRSA) is a multidrug‐resistant opportunistic pathogen with a great ability to form biofilms. Herein, the antimicrobial potential of Thymbra capitata essential oil (EO) against MRSA biofilms was investigated. The determination of the minimum inhibitory concentration (MIC) and the minimum lethal concentration (MLC) of the T. capitata EO was first investigated on a group of clinical isolates from septicaemias, diabetic foot ulcers and osteomyelitis. Biofilms were incub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Besides this, antimicrobial resistance is a great challenge in current medicine [34]. Some traditionally used medicinal plants have essential oils which are effectively active against multiple pathogenic microorganisms including methicillin-resistant bacterial strains [35][36][37] Despite their use, they do have disadvantages of lack of dosage instruction, and missing scientific proof for their claim [38].…”
Section: Discussionmentioning
confidence: 99%
“…Besides this, antimicrobial resistance is a great challenge in current medicine [34]. Some traditionally used medicinal plants have essential oils which are effectively active against multiple pathogenic microorganisms including methicillin-resistant bacterial strains [35][36][37] Despite their use, they do have disadvantages of lack of dosage instruction, and missing scientific proof for their claim [38].…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, Alabdullatif et al tested the biofilm-killing efficiency of three concentrations of Tunisian T. capitatus EO (10, 20, and 30% v / v ) against Staphylococcus epidermidis biofilms (preformed on 96-well PS microtiter plates at 37 °C for 24 h) following 30 s of application (to mimic skin-disinfection practices), and they observed log reductions that ranged from 1.17 ± 0.12 to 1.42 ± 0.10 log 10 CFU/mL [ 36 ]. Almeida et al tested the biofilm-disrupting efficiency of T. capitata EO collected from plants grown in the south of Portugal against preformed biofilms (on 96-well PS microtiter plates at 37 °C for 24 h) of six clinical methicillin-resistant S. aureus (MRSA) isolates by exposing them for 24 h (at 37 °C) to 0.64 μg/mL of the EO (a concentration that was equal to its MBC) [ 37 ]. The action of the EO in that study was also compared with the action of two antibiotics with distinct mechanisms of action and commonly used to treat MRSA infections (ciprofloxacin and tetracycline) and tested at their respective peak serum concentrations [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Almeida et al tested the biofilm-disrupting efficiency of T. capitata EO collected from plants grown in the south of Portugal against preformed biofilms (on 96-well PS microtiter plates at 37 °C for 24 h) of six clinical methicillin-resistant S. aureus (MRSA) isolates by exposing them for 24 h (at 37 °C) to 0.64 μg/mL of the EO (a concentration that was equal to its MBC) [ 37 ]. The action of the EO in that study was also compared with the action of two antibiotics with distinct mechanisms of action and commonly used to treat MRSA infections (ciprofloxacin and tetracycline) and tested at their respective peak serum concentrations [ 37 ]. The biofilm cells of all tested isolates were significantly affected in their culturability and metabolic activity after incubation with the EO, with an observed average reduction of 2.6 log 10 CFU/mL, significantly higher than that observed with the tested antibiotics (for both, an average reduction of less than of 0.5 log 10 CFU/mL was observed).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antimicrobial activities of the plant species have been reported to be effective against P. vulgaris, E. coli, P. mirabilis, B.subtilis, S. aureus, Salmonella enterica subsp. enterica serovar Typhimurium, L. monocytogenes, Candida spp., K. pneumoniae, S. boydii, P. aeruginosa and B. cereus (Almeida et al, 2022;Charfi et al, 2019;de-Oliveira et al, 2012;Faleiro et al, 2005;Hepokur et al, 2020b;Karampoula et al, 2016;Merino et al, 2019;Moukhles et al, 2020). In a different study, it was reported that it has an antigiardia effect against Giardia trophozoites (Machado et al, 2010).…”
Section: T Sintenisii Subsp Isaurica Phdavismentioning
confidence: 99%